Production of Bagasse-Based Natrium Ligno Sulfonat (Nals) Surfactant for Chemical Flooding - Emmy Fatmi Budhya; Muhammad Taufiq Fathaddin; Sugiatmo Kasmungin (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Oil recovery may be increased by lowering interfacial tension between oil and water due to surfactant injection. Bagasse is one of the organic materials which has a fairly high lignin content, where lignin is the basic substance of making Natrium Lignosulfonate (NaLS) Surfactants. The research was divided into three sections. The first was experiment to produce lignin from bagasse. In this experiment 100 gram of bagasse with size of 60 mesh or 80 mesh extracted by benzene + ethanol (2:1) and then 20%, 50%, or 75% NaOH was added to activate lignin. The maximum amount of lignin produced was 24.88%. The second experiment was to produce NaLS surfactant from obtained lignin. FTIR equipment was used to verify the NaLS surfactant yielded using the method. The maximum amount of NaLS surfactant produced was 20.264% of bagasse mass. After that NaLS surfactant obtained from the previous process was used in chemical flooding experiment. In the experiments, the surfactant concentration in the solution was varied at 0.05%, 0.10%, 0.15%, and 1.00%. While temperature was set at 30°C, 40°C, 60°C, 70°C, or 80°C. The optimum condition happened when a solution with surfactant concentration of 1% was injected at 60°C. The recovery factor of oil using the condition was 0.47.